Effects of Slug Size, Soaking, and Injection Schemes on the Performance of Controlled Ions Water Flooding in Carbonates - Moradpour, N. (American Chemical Society, 2020)
The results of many previous studies on low salinity/controlled ions water (CIW) flooding suggest that future laboratory and modeling investigations are required to comprehensively understand and interpret the achieved observations. In this work, the aim is co-optimization of the length of the injected slug and soaking time in the CIW flooding process. Furthermore, the possibility of the occurrence of several governing mechanisms is studied. Therefore, the experimental results were utilized to develop a compositional model, using CMG GEM software, in order to obtain the relative permeability curves by history matching. It was concluded that CIW slug injection, concentrated in the potential-determining ion, can increase oil recovery under a multi ion exchange (MIE) mechanism. The wettability of the carbonate rocks was changed from a mixed or oil wet state toward more water wetness. However, there is a CIW slug length, beyond which extending the length does not significantly improve the rock wettability, and consequently, the oil production, which is known as the optimum slug size. This implies that the optimization of the injection process, by minimizing the slug size, can decrease the need for the CIW supply, therefore lowering the process expenditure. Moreover, if the exposure time of the rock and CIW is increased (soaking), a higher level of ion substitution is probable, leading to more oil detachment and production. Rock dissolution/precipitation (leading to a pH change) was found to have a negligible contribution. Copyright Â© 2020 American Chemical Society.